Gender and Welfare Service Work in Biocapitalism Lean in Action - Jokinen, Eeva (Taylor & Francis, 2024)
This book explores how Lean - a global management doctrine - operates and is adopted in the real, corporeal, collective, and affective environments of health and social care services. During Lean implementation processes, knowledges, affects, skills, and materialities come together in manifold, complex ways. Based on ethnographic fieldwork, interviews, and observation, and with empirical and theoretical rigour, the book provides an answer to the question of what happens to care work when processes become 'Leaned'. As in many other fields, the predominantly female health and social care sectors suffer from devaluation in terms of wages and working conditions. The book explores how Lean management is ultimately lived in this gendered context of work and labour. Moreover, the book situates Lean and related management doctrines in the current mutation of capitalism - that is, biocapitalism - in which bios, life itself, becomes the core of value production. The book adds to the corpus of work, organisation, and management studies on Lean that have rarely focused on gender, affect, or sociomateriality. It provides scholars in Social Science, Management, and Gender Studies with a fresh outlook and a cross-disciplinary take on Lean management.